An atomic spin precession detection method based on electro-optic modulation in an all-optical K–Rb hybrid atomic magnetometer. (9th June 2017) - Hu, Yanhui; Liu, Xuejing; Li, Yang; Yao, Han; Dai, Lingling; Yang, Biyao; Ding, Ming
Abstract: We present an ultrahigh-sensitivity electro-optic modulator (EOM) detection method for detecting the atomic Larmor precession in an all-optical K–Rb hybrid atomic magnetometer operating in the spin-exchange relaxation-free regime. A magnetic field sensitivity of 10 f T Hz −1/2 has been achieved by optimizing the probe laser parameters and the EOM modulation conditions, which is comparable to that with the Faraday modulation method and has a better performance than the balanced polarimetry method in the low frequency range. The EOM detection method in the atomic magnetometer presents several advantages, such as simple structure, no extra magnetic noise, moderate thermal effect, high measurement sensitivity and reliable stability. It is demonstrated to be feasible for the improved compactness and simplicity of atomic magnetic field measurement devices in the future.